Multimodal Imaging for Total Anomalous Systemic Venous Drainage Diagnosis and Preoperative Planning: A Case Report and Literature Review - Ding, Mingyan; Zhang, Huihui; Sun, Dandan; Li, Qiang; Jiao, Ni; Zhu, Fang (Frontiers in Cardiovascular Medicine, 2022)
Total anomalous systemic venous connection (TASVC) is a rare congenital heart malformation. Here we report a case of 40-year-old male patient who has total anomalous systemic venous connection. It was diagnosed as TASVC for the first time through multimodal imaging combined TTE, TEE and three-dimensional (3D-TTE) echocardiography, contrast echocardiography and computed tomography angiography (CTA). We review 15 published reports of TASVC and summarize the ultrasonographic characteristics. After repair through ectopic venous drainage in cardiac surgery, the patient’s cyanosis symptoms were alleviated greatly. Echocardiography was the first-line examination of TASVC. Multimodal imaging combined TTE, TEE, 3D TEE, contrast echocardiography and CTA was necessary for confirmed diagnosis of TASVC.